2008
DOI: 10.1542/peds.2007-1788
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Vitamin K Deficiency Bleeding in Breastfed Infants: Lessons From the Dutch and Danish Biliary Atresia Registries

Abstract: A daily dose of 25 microg of vitamin K fails to prevent bleedings in apparently healthy infants with unrecognized cholestasis because of biliary atresia. One milligram of weekly oral prophylaxis offers significantly higher protection to these infants and is of similar efficacy as 2 mg of intramuscular prophylaxis at birth. Our data underline the fact that event analysis in specific populations at risk can help to evaluate and improve nationwide prophylactic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 26 publications
4
68
0
8
Order By: Relevance
“…Previous studies showed that a weekly oral prophylaxis of 1 mg vitamin K in the first 3 months of life was highly effective in preventing VKDB. 13,22 The hypothesis at that time was that a weekly prophylaxis of 1 mg was more effective than 25 μg daily prophylaxis, as the cumulative dose per week was 6-fold higher in the weekly prophylaxis (1.05 vs 0.175 mg). Our present data clearly show that this hypothesis needs to be rejected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that a weekly oral prophylaxis of 1 mg vitamin K in the first 3 months of life was highly effective in preventing VKDB. 13,22 The hypothesis at that time was that a weekly prophylaxis of 1 mg was more effective than 25 μg daily prophylaxis, as the cumulative dose per week was 6-fold higher in the weekly prophylaxis (1.05 vs 0.175 mg). Our present data clearly show that this hypothesis needs to be rejected.…”
Section: Discussionmentioning
confidence: 99%
“…13,18 In the current study, we used these data, enriched with updated results on the new regimens, to compare the efficacy of the adaptation with regard to protection against VKDB.…”
Section: Vitamin K Prophylaxismentioning
confidence: 99%
See 2 more Smart Citations
“…Administration method (oral/intramuscular), duration, and dose differ from country to country. 3,4,14,15,18) However, recent epidemiological studies have provided a more reliable prophylactic method. Comparison of the risks of vitamin K deficiency bleeding under different prophylactic regimens in infants with biliary atresia found that a daily dose of 25 mg of vitamin K failed to prevent bleeding, but weekly oral administration of 1 mg of vitamin K offered significantly higher protection to these infants and provided similar efficiency to 2 mg of intramuscular prophylaxis at birth.…”
Section: Discussionmentioning
confidence: 99%